Blind speech signals separation based on Borel measure peaks for under-determined mixtures - GUO Wen-qiang1; QIU Tian-shuang1; ZHA Dai-feng1 (Tongxin xuebao, 2007)
The statistical characteristics of stable distribution was briefly introduced,and a new method for identifying the independent components of an Alpha-stable random vector for under-determined mixtures was proposed.The method was based on an estimate of the discrete spectral measure for the characteristic function of an Alpha-stable random vector.Simulations demonstrate that the proposed method can identify independent components and the basis vectors of mixing matrix in the so-called under-determined case of more sources than mixtures,and obtained the good effect in the speech signals separation application.